2013
DOI: 10.1177/1057083713512837
|View full text |Cite
|
Sign up to set email alerts
|

Beginning Music Teacher Mentor Practices

Abstract: The purpose of this inquiry was to examine the current reflections of 13 experienced teachers on their past perceptions of mentoring as documented by Conway (2003a). Participants read the 2003 study and examined all data collected in 1999-2000, including journals, two questionnaires, individual interviews, focus group interviews, mentor interviews, and principal interviews. They then wrote an e-mail reflection on that reading and participated in an individual interview regarding their current perceptions on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…While retrospection may be biased insofar as it is selective (Gonzales-Morganti, Lovejoy, Burke-Beckjord, Haviland, Haas, & Farley, 2013), and general as opposed to detailed (Brewin et al, 1993), it also has the potential of enhancing comprehension of complex circumstances from a more mature perspective (Cherubini, Kitchen, Goldblatt, & Smith, 2011). A recent follow-up study by Conway (2013) provides some support for this assertion. In a study of music teachers 10 years after participating in an induction program she found that their retrospective views concurred with their earlier reflections while at the same time they demonstrated a deeper understanding of the needs of inductee teachers that was related to more experience in the field.…”
mentioning
confidence: 52%
“…While retrospection may be biased insofar as it is selective (Gonzales-Morganti, Lovejoy, Burke-Beckjord, Haviland, Haas, & Farley, 2013), and general as opposed to detailed (Brewin et al, 1993), it also has the potential of enhancing comprehension of complex circumstances from a more mature perspective (Cherubini, Kitchen, Goldblatt, & Smith, 2011). A recent follow-up study by Conway (2013) provides some support for this assertion. In a study of music teachers 10 years after participating in an induction program she found that their retrospective views concurred with their earlier reflections while at the same time they demonstrated a deeper understanding of the needs of inductee teachers that was related to more experience in the field.…”
mentioning
confidence: 52%
“…The teachers identified these activities in daily reflections, end-of-course reflections, and individual interviews. Participants in Bowles (2002) and Conway (2015) also found these activities important. LUSD teachers believed that carefully-developed curricula and rubrics would increase rigor in their instruction and bolster student achievement.…”
Section: Discussionmentioning
confidence: 96%
“…Teacher choice may be an important feature of professional development due to their varying needs (Conway et al, 2005; Schmidt & Robbins, 2011; Stanley et al, 2014). Bauer et al (2009) said that “as music educators progress though their careers, it appears their professional development requirements and interests evolve” (p. 121), a statement supported by other researchers (Conway, 2007, 2008, 2015; Eros, 2011; Hammel, 2007). Appropriate professional development should be congruent with the career stage of the teacher (Eros, 2011; Hammel, 2007).…”
mentioning
confidence: 98%
“…While these suggestions might be common knowledge for some, it is crucial that we, as professional music educators and mentors, advocate for and request such support from our own school districts, state music educators associations, and university teacher-preparation programs. 39 Assigning mentors and mentees to teach in the same school is optimal but might not be realistic for those in small schools or for those who teach at the elementary level. Release time for travel will help alleviate this potential problem.…”
Section: Supporting Music Teacher Mentorsmentioning
confidence: 99%